High-strength light-weight extra-high voltage electric porcelain body and preparation method thereof
Patent Information
- Application Number
- CN202411659860.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-11-20
AI Technical Summary
随着电瓷行业在我国的迅速发展,行业一直沿用的优质可塑性黏土原料日益贫乏,然而输变电事业的发展,对电瓷绝缘子的性能要求越来越高,产品结构更加复杂,其成型加工过程对坯料泥料的强度和可塑性能要求也越来越高,仅靠黏土原料已不能满足产品制造加工过程对坯料强度和可塑性的要求
[0012]本发明的有益效果在于:采用本发明所述方法制备的电瓷坯料具有良好的强度,能够有效地保证后续修坯、上釉、装窑等工序的顺利进行,减少破损率,降低生产加工成本。本发明首先通过在硅的氧化物中掺杂铈元素,所获得的掺杂二氧化硅粉末具有较高的比表面积,一方面显著增加了后续坯料中二氧化硅粉末和其他组分的结合面,另一方面也为后续的表面修饰做准备。然后在通过鞣酸改性,在粉末表面形成大分子结构,使得二氧化硅和黏土颗粒间的结合力增强,从而提高坯体的强度。后续经过接枝β-环糊精,能够进一步地提高二氧化硅与其他组分颗粒之间的交联作用,形成以改性二氧化硅粉末为连接单元的不规则网状结构,对坯体的强度具有良好的改善效果。
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrical porcelain blank material technology, and in particular to a high-strength, lightweight ultra-high voltage electrical porcelain blank and its preparation method. Background Technology
[0002] Unlike other ceramic products, electrical porcelain insulators, due to their unique product structure and manufacturing process, require high strength and plasticity of the raw materials. With the rapid development of the electrical porcelain industry in my country, the availability of high-quality, plastic clay raw materials, which have been the industry's mainstay, is increasingly scarce. Meanwhile, the development of power transmission and transformation projects places increasingly higher demands on the performance of electrical porcelain insulators, resulting in more complex product structures. The molding and processing of these insulators also places increasingly higher demands on the strength and plasticity of the raw materials. Clay raw materials alone can no longer meet the strength and plasticity requirements of the manufacturing process. Summary of the Invention
[0003] Therefore, this invention provides a high-strength, lightweight ultra-high voltage electric porcelain blank, the raw materials of which include clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; wherein the modified silica powder is prepared by:
[0004] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60±5℃ and keep it at that temperature, and reflux during the holding process; then add the mixture of ammonia and ethanol and the aqueous solution of cerium nitrate to the ethanol solution of tetraethyl orthosilicate while stirring, and continue stirring at 60±5℃ for 80-100 min after the addition is completed, and then let it stand at room temperature for more than 5 h to separate the solid and liquid, wash the solid phase with deionized water more than 3 times, and then dry it at 200℃ for more than 3 h to obtain doped silica powder;
[0005] (2) Add the doped silica powder to an aqueous solution of ethanol and stir and disperse it under ultrasonic conditions for more than 20 minutes to obtain a dispersion. Then, add tannic acid to the dispersion under stirring. After the addition is completed, adjust the pH of the dispersion to 4-6. Then heat it in a water bath to 80±5℃ and stir it at a constant temperature for more than 60 minutes. After stirring, separate the solid and liquid phases. Wash the solid phase with deionized water more than 3 times and dry it at 80℃ for more than 3 hours to obtain the modified powder.
[0006] (3) Prepare a solution of β-cyclodextrin in N,N-dimethylformamide, stir the solution of β-cyclodextrin in N,N-dimethylformamide, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is completed, continue stirring the solution for more than 2 hours. Then add the modified powder to the solution while stirring. After the addition is completed, continue stirring for more than 15 hours. Then perform solid-liquid separation. The solid phase is first washed with N,N-dimethylformamide more than twice, and then washed with deionized water more than twice to obtain the modified silica powder.
[0007] Further, the raw materials are as follows by weight: 100 parts clay, 20-30 parts porcelain powder, 20-25 parts modified silica powder, 24-28 parts potassium feldspar, 16-20 parts bauxite powder, 0.6-0.8 parts humic acid, and 6-10 parts titanium dioxide powder.
[0008] Further, in step (1), the ethanol solution of tetraethyl orthosilicate contains 5% to 6% tetraethyl orthosilicate by mass and ethanol as the solvent; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia to anhydrous ethanol of 2 to 3 to 1; and the aqueous solution of cerium nitrate contains 8 to 10 g / L of cerium nitrate.
[0009] Further, in step (1), the volume ratio of the mixture of ammonia and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is ethanol solution of tetraethyl orthosilicate: mixture of ammonia and ethanol: aqueous solution of cerium nitrate = 10:4~5:1~2.
[0010] Further, in step (2), the mass ratio of the doped silica powder added to the aqueous ethanol solution is 1:30-40; wherein the volume percentage of ethanol in the aqueous ethanol solution is 80%-85%, and the remainder is water; the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is 1:0.5-0.8.
[0011] Further, in step (3), the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 16-20 g / L, and the solvent is N,N-dimethylformamide; the mass ratio of the added 1,1'-carbonyldiimidazole and the modified powder to the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3-4 g: 1-3 g: 100 mL.
[0012] The beneficial effects of this invention are as follows: the electrical porcelain blank prepared by the method described in this invention has good strength, which can effectively ensure the smooth progress of subsequent processes such as blank trimming, glazing, and kiln loading, reduce breakage rate, and lower production and processing costs. This invention first dopes silicon oxide with cerium, resulting in doped silica powder with a high specific surface area. This significantly increases the bonding surface between silica powder and other components in the subsequent blank, and also prepares for subsequent surface modification. Then, tannic acid modification forms a macromolecular structure on the powder surface, enhancing the bonding force between silica and clay particles, thereby improving the strength of the blank. Subsequent grafting with β-cyclodextrin further enhances the cross-linking effect between silica and other component particles, forming an irregular network structure with modified silica powder as the connecting unit, which has a good effect on improving the strength of the blank. Detailed Implementation
[0013] The present invention will be further described below with reference to the embodiments.
[0014] Example 1
[0015] A high-strength, lightweight ultra-high voltage electric porcelain blank, comprising clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; the raw materials, by weight, are: 100 parts clay, 20 parts porcelain powder, 20 parts modified silica powder, 24 parts potassium feldspar, 16 parts bauxite powder, 0.6 parts humic acid, and 6 parts titanium dioxide powder. The modified silica powder is prepared by:
[0016] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 2:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 8 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:4:1. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0017] (2) The doped silica powder is added to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the remainder is water; the mixture is stirred and dispersed under ultrasonic conditions for 20 min to obtain a dispersion; then tannic acid is added to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added during the preparation of the dispersion is 1:0.5; after the addition is completed, the pH of the dispersion is adjusted to 5 (using acetic acid or ammonia water with a solute mass fraction of 20%), and then heated to 80°C in a water bath and stirred at a constant temperature for 60 min. After stirring, the solid and liquid are separated, the solid phase is washed 3 times with deionized water and dried at 80°C for 3 h to obtain the modified powder;
[0018] (3) Prepare an N,N-dimethylformamide solution of β-cyclodextrin, wherein the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 16 g / L and the solvent is N,N-dimethylformamide; stir the N,N-dimethylformamide solution of β-cyclodextrin, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is completed, continue stirring the solution for 2 hours, and then add the modified powder to the solution while stirring. The mass ratio of the added 1,1'-carbonyldiimidazole, the modified powder, and the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3g: 1g: 100mL. After the addition is completed, stirring is continued for 15h, followed by solid-liquid separation. The solid phase is first washed twice with N,N-dimethylformamide, and then washed twice with deionized water to obtain the modified silica powder.
[0019] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0020] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0021] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0022] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank.
[0023] Example 2
[0024] A high-strength, lightweight ultra-high voltage electric porcelain blank, comprising clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; the raw materials, by weight, are: 100 parts clay, 24 parts porcelain powder, 22 parts modified silica powder, 26 parts potassium feldspar, 18 parts bauxite powder, 0.7 parts humic acid, and 8 parts titanium dioxide powder. The modified silica powder is prepared by:
[0025] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 5%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 2:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:4:1. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0026] (2) The doped silica powder is added to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the remainder is water; the mixture is stirred and dispersed under ultrasonic conditions for 20 min to obtain a dispersion; then tannic acid is added to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added during the preparation of the dispersion is 1:0.6; after the addition is completed, the pH of the dispersion is adjusted to 5 (using acetic acid or ammonia water with a solute mass fraction of 20%), and then heated to 80°C in a water bath and stirred at a constant temperature for 60 min. After stirring, the solid and liquid are separated, the solid phase is washed 3 times with deionized water and dried at 80°C for 3 h to obtain the modified powder;
[0027] (3) Prepare an N,N-dimethylformamide solution of β-cyclodextrin, wherein the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 18 g / L and the solvent is N,N-dimethylformamide; stir the N,N-dimethylformamide solution of β-cyclodextrin, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is completed, continue stirring the solution for 2 hours, and then add the modified powder to the solution while stirring. The mass ratio of the added 1,1'-carbonyldiimidazole, the modified powder, and the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3g: 2g: 100mL. After the addition is completed, stirring is continued for 15h, followed by solid-liquid separation. The solid phase is first washed twice with N,N-dimethylformamide, and then washed twice with deionized water to obtain the modified silica powder.
[0028] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0029] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0030] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0031] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank.
[0032] Example 3
[0033] A high-strength, lightweight ultra-high voltage electric porcelain blank, comprising clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; the raw materials, by weight, are: 100 parts clay, 28 parts porcelain powder, 24 parts modified silica powder, 26 parts potassium feldspar, 18 parts bauxite powder, 0.7 parts humic acid, and 8 parts titanium dioxide powder. The modified silica powder is prepared by:
[0034] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back to the ethanol solution during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:5:2. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0035] (2) The doped silica powder is added to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the remainder is water; the mixture is stirred and dispersed under ultrasonic conditions for 20 min to obtain a dispersion; then tannic acid is added to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added during the preparation of the dispersion is 1:0.7; after the addition is completed, the pH of the dispersion is adjusted to 5 (using acetic acid or ammonia water with a solute mass fraction of 20%), and then heated to 80°C in a water bath and stirred at a constant temperature for 60 min. After stirring, the solid and liquid are separated, the solid phase is washed 3 times with deionized water and dried at 80°C for 3 h to obtain the modified powder;
[0036] (3) Prepare an N,N-dimethylformamide solution of β-cyclodextrin, wherein the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 18 g / L and the solvent is N,N-dimethylformamide; stir the N,N-dimethylformamide solution of β-cyclodextrin, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is completed, continue stirring the solution for 2 hours, and then add the modified powder to the solution while stirring. The mass ratio of the added 1,1'-carbonyldiimidazole, the modified powder, and the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 4g: 2g: 100mL. After the addition is completed, stirring is continued for 15h, followed by solid-liquid separation. The solid phase is first washed twice with N,N-dimethylformamide, and then washed twice with deionized water to obtain the modified silica powder.
[0037] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0038] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0039] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0040] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank.
[0041] Example 4
[0042] A high-strength, lightweight ultra-high voltage electric porcelain blank, comprising clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; the raw materials, by weight, are: 100 parts clay, 30 parts porcelain powder, 25 parts modified silica powder, 28 parts potassium feldspar, 20 parts bauxite powder, 0.8 parts humic acid, and 10 parts titanium dioxide powder. The modified silica powder is prepared by:
[0043] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 10 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back to the ethanol solution during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:5:2. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0044] (2) The doped silica powder is added to an aqueous solution of ethanol, wherein the mass ratio of the doped silica powder to the aqueous solution of ethanol is 1:30; wherein the volume percentage of ethanol in the aqueous solution of ethanol is 80%, and the remainder is water; the mixture is stirred and dispersed under ultrasonic conditions for 20 min to obtain a dispersion; then tannic acid is added to the dispersion under stirring, wherein the mass ratio of the added tannic acid to the mass of the doped silica powder added during the preparation of the dispersion is 1:0.8; after the addition is completed, the pH of the dispersion is adjusted to 5 (using acetic acid or ammonia water with a solute mass fraction of 20%), and then heated to 80°C in a water bath and stirred at a constant temperature for 60 min. After stirring, the solid and liquid are separated, the solid phase is washed 3 times with deionized water and dried at 80°C for 3 h to obtain the modified powder;
[0045] (3) Prepare an N,N-dimethylformamide solution of β-cyclodextrin, wherein the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 20 g / L, and the solvent is N,N-dimethylformamide; stir the N,N-dimethylformamide solution of β-cyclodextrin, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is complete, continue stirring the solution for 2 hours, and then add the modified powder to the solution while stirring. The mass ratio of the added 1,1'-carbonyldiimidazole, the modified powder, and the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 4 g: 3 g: 100 mL. After the addition is completed, stirring is continued for 15 h, followed by solid-liquid separation. The solid phase is first washed twice with N,N-dimethylformamide, and then washed twice with deionized water to obtain the modified silica powder.
[0046] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0047] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0048] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0049] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank.
[0050] Comparative Example 1
[0051] A comparative electrical porcelain blank comprises clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder. The raw materials, by weight, are: 100 parts clay, 28 parts porcelain powder, 24 parts modified silica powder, 26 parts potassium feldspar, 18 parts bauxite powder, 0.7 parts humic acid, and 8 parts titanium dioxide powder. The modified silica powder is prepared by:
[0052] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back to the ethanol solution during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:5:2. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0053] (2) Prepare an N,N-dimethylformamide solution of β-cyclodextrin, wherein the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 18 g / L, and the solvent is N,N-dimethylformamide; stir the N,N-dimethylformamide solution of β-cyclodextrin, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is complete, continue stirring the solution for 2 hours, and then add the doped silica powder to the solution while stirring. The mass ratio of 1'-carbonyldiimidazole, the doped silica powder, and the N,N-dimethylformamide solution of β-cyclodextrin was 1,1'-carbonyldiimidazole:doped silica powder:N,N-dimethylformamide solution of β-cyclodextrin = 4g:2g:100mL. After the addition was completed, the mixture was stirred for 15h, and then the solid and liquid phases were separated. The solid phase was washed twice with N,N-dimethylformamide and then twice with deionized water to obtain the modified silica powder of this comparative example.
[0054] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0055] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0056] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0057] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank described in this comparative example.
[0058] Comparative Example 2
[0059] A comparative electrical porcelain blank comprises clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder. The raw materials, by weight, are: 100 parts clay, 28 parts porcelain powder, 24 parts modified silica powder, 26 parts potassium feldspar, 18 parts bauxite powder, 0.7 parts humic acid, and 8 parts titanium dioxide powder. The modified silica powder is prepared by:
[0060] (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; in the ethanol solution of tetraethyl orthosilicate, the mass percentage of tetraethyl orthosilicate is 6%, and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 3:1; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 9 g / L, and the solvent is water; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60°C and keep it at that temperature, condensing back to the ethanol solution during the heat treatment process. The mixture of ammonia and ethanol and the aqueous solution of cerium nitrate were simultaneously added to the ethanol solution of tetraethyl orthosilicate under stirring. The volume ratio of the mixture of ammonia and ethanol to the aqueous solution of cerium nitrate was 10:5:2. After the addition was completed, the mixture was stirred at 60°C for 80 minutes, then allowed to stand at room temperature for 5 hours. The solid and liquid phases were separated, and the solid phase was washed three times with deionized water and then dried at 200°C for 3 hours to obtain doped silica powder.
[0061] (2) The doped silica powder was added to an aqueous solution of ethanol, and the mass ratio of the doped silica powder to the aqueous solution of ethanol was 1:30. The volume percentage of ethanol in the aqueous solution of ethanol was 80%, and the remainder was water. The mixture was stirred and dispersed under ultrasonic conditions for 20 min to obtain a dispersion. Then, tannic acid was added to the dispersion under stirring, and the mass ratio of the added tannic acid to the mass of the doped silica powder added during the preparation of the dispersion was 1:0.7. After the addition was completed, the pH of the dispersion was adjusted to 5 (using acetic acid or ammonia water with a solute mass fraction of 20%). Then, the mixture was heated to 80°C in a water bath and stirred at a constant temperature for 60 min. After stirring, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 3 h to obtain the modified silica powder of this comparative example.
[0062] The preparation method of the above-mentioned electrical porcelain blank is as follows:
[0063] Step 1: Weigh each raw material according to the above weight proportions, mix the raw materials in a ball mill, add water and ball mill at a speed of 100 r / min, the material-ball-water mass ratio is material:ball:water = 1:1.5:1, and the ball milling time is 10 h.
[0064] Step 2: The mixed mud is vacuum-refined in a mud refining machine with the air pressure set to 0.06 MPa;
[0065] Step 3: After refining the mud, adjust the water content of the mud slurry to 21 wt%, then pour it into a mold to form the shape of an electric porcelain; then dry it to a water content of 0.1 wt%, demold it, and form the electric porcelain blank described in this comparative example.
[0066] Example 5
[0067] The dry blank strength of the electrical porcelain blanks prepared by the methods described in the above embodiments and comparative examples was tested, and the results are shown in Table 1.
[0068] As shown in Table 1, the electrical porcelain blanks prepared using the method described in this invention exhibit good strength, effectively ensuring the smooth progress of subsequent processes such as blank trimming, glazing, and kiln loading, reducing breakage rates, and lowering production costs. This invention first dopes silicon oxide with cerium, resulting in doped silica powder with a high specific surface area. This significantly increases the bonding surface between silica powder and other components in the blank, and also prepares for subsequent surface modification. Then, tannic acid modification forms a macromolecular structure on the powder surface, enhancing the bonding force between silica and clay particles, thereby improving the strength of the blank. Subsequent grafting with β-cyclodextrin further enhances the cross-linking effect between silica and other component particles, forming an irregular network structure with modified silica powder as the connecting unit, which effectively improves the strength of the blank.
[0069] Table 1
[0070] Example 1 8.11 Example 2 8.19 Example 3 8.23 Example 4 8.15 Comparative Example 1 6.27 Comparative Example 2 6.50
[0071] The technical solutions provided by the present invention have been described in detail above. For those skilled in the art, there will be changes in specific implementation methods and application scope based on the ideas of the embodiments of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A high-strength, lightweight ultra-high voltage electric porcelain blank, characterized in that, The raw materials include clay, porcelain powder, modified silica powder, potassium feldspar, bauxite powder, humic acid, and titanium dioxide powder; the raw materials, by weight, are: 100 parts clay, 20-30 parts porcelain powder, 20-25 parts modified silica powder, 24-28 parts potassium feldspar, 16-20 parts bauxite powder, 0.6-0.8 parts humic acid, and 6-10 parts titanium dioxide powder; wherein the modified silica powder is prepared by: (1) Prepare an ethanol solution of tetraethyl orthosilicate; prepare a mixture of ammonia and ethanol; prepare an aqueous solution of cerium nitrate; heat the ethanol solution of tetraethyl orthosilicate in a water bath to 60±5℃ and keep it at that temperature, and reflux during the holding process; then add the mixture of ammonia and ethanol and the aqueous solution of cerium nitrate to the ethanol solution of tetraethyl orthosilicate while stirring, and continue stirring at 60±5℃ for 80-100 min after the addition is completed, and then let it stand at room temperature for more than 5 h to separate the solid and liquid, wash the solid phase with deionized water more than 3 times, and then dry it at 200℃ for more than 3 h to obtain doped silicon dioxide powder; (2) The doped silica powder is added to an aqueous solution of ethanol and stirred and dispersed under ultrasonic conditions for more than 20 minutes to obtain a dispersion. Then, tannic acid is added to the dispersion under stirring. After the addition is completed, the pH of the dispersion is adjusted to 4-6. Then, the dispersion is heated to 80±5℃ in a water bath and stirred at a constant temperature for more than 60 minutes. After stirring, the solid and liquid are separated. The solid phase is washed with deionized water more than 3 times and dried at 80℃ for more than 3 hours to obtain the modified powder. (3) Prepare a solution of β-cyclodextrin in N,N-dimethylformamide, stir the solution of β-cyclodextrin in N,N-dimethylformamide, and then add 1,1'-carbonyldiimidazole to the solution while stirring. After the addition is completed, continue stirring the solution for more than 2 hours. Then add the modified powder to the solution while stirring. After the addition is completed, continue stirring for more than 15 hours. Then perform solid-liquid separation. The solid phase is first washed with N,N-dimethylformamide more than twice, and then washed with deionized water more than twice to obtain the modified silica powder.
2. The high-strength, lightweight ultra-high voltage electrical porcelain blank according to claim 1, characterized in that, In step (1), the ethanol solution of tetraethyl orthosilicate has a mass percentage of 5% to 6% and the solvent is ethanol; the mixture of ammonia and ethanol is prepared by mixing ammonia with a solute mass percentage of 25% and anhydrous ethanol in a volume ratio of ammonia:anhydrous ethanol = 2 to 3:1; the aqueous solution of cerium nitrate has a concentration of 8 to 10 g / L.
3. The high-strength, lightweight ultra-high voltage electrical porcelain blank according to claim 2, characterized in that, In step (1), the volume ratio of the mixture of ammonia and ethanol and the aqueous solution of cerium nitrate added to the ethanol solution of tetraethyl orthosilicate is 10:4~5:1~2.
4. The high-strength, lightweight ultra-high voltage electric porcelain blank according to claim 1, characterized in that, In step (2), the mass ratio of the doped silica powder added to the aqueous ethanol solution is 1:30-40; wherein the volume percentage of ethanol in the aqueous ethanol solution is 80%-85%, and the remainder is water; the mass ratio of the added tannic acid to the mass of the doped silica powder added when preparing the dispersion is 1:0.5-0.
8.
5. The high-strength, lightweight ultra-high voltage electrical porcelain blank according to claim 1, characterized in that, In step (3), the concentration of β-cyclodextrin in the N,N-dimethylformamide solution is 16-20 g / L, and the solvent is N,N-dimethylformamide; the mass ratio of the added 1,1'-carbonyldiimidazole and the modified powder to the volume ratio of the N,N-dimethylformamide solution of β-cyclodextrin is 1,1'-carbonyldiimidazole: modified powder: N,N-dimethylformamide solution of β-cyclodextrin = 3-4 g: 1-3 g: 100 mL.
Citation Information
Patent Citations
Preparation method of tannic acid grafted glass flakes and application of tannic acid grafted glass flakes in high-solid anticorrosive coating
CN112226101A
Method for preparing white carbon black modified by silane coupling agent
WO2012162937A1